Progress in RNAi-mediated Molecular Therapy of Acute and Chronic Myeloid Leukemia - Breanne Landry; Juliana Valencia-Serna; Hilal Gul-Uludag; Xiaoyan Jiang; Anna Janowska-Wieczorek; Joseph Brandwein; Hasan Uludag (Elsevier, 2015)
Leukemias arise from genetic alterations in normal hematopoietic stem or progenitor cells, leading to impaired regulation of proliferation, differentiation, apoptosis, and survival of the transformed cells. With the advent of RNA interference (RNAi) and the short interfering RNA (siRNA) as its pharmacological mediator, it is becoming possible to modulate specific targets at will. This article summarizes current attempts to utilize RNAi reagents for therapy of leukemias, focusing on acute and chronic myeloid leukemia. We first present unique aspects of RNAi-mediated therapy, followed by a brief background on the delivery technology of RNAi reagents. The need for leukemia-specific delivery of siRNA is discussed by describing approaches that targeted agents to leukemic cells. Pharmacokinetics and biodistribution of RNAi agents are then presented, highlighting the critical issues pertinent to emerging siRNA therapy. Efforts to deliver specific RNAi therapies are then summarized in the context of expected clinical outcomes, focusing on limiting leukemic cell survival, sensitizing malignant cells to chemotherapy, mobilization of leukemic cells, and eradication of leukemic stem cells. We conclude with a perspective on the future of RNAi therapy, emphasizing the technological requirements and mechanistic challenges for clinical entry.